SD-6LN: improved existing internet of things framework by incorporating software defined network approach. (20th August 2022) - Das, Rohit Kumar; Maji, Arnab Kumar; Saha, Goutam
The Internet of Things (IoT) is one of the prominent technologies in today's world, where its real-time applications are being utilised in various areas. In spite of the fact that the advancement made by IoT is highly remarkable, the current IoT foundation experiences confinements such as availability, reliability, scalability, resiliency, interoperability, security and privacy. Software-Defined Network (SDN) is an approach that can help in resolving many of the IoT limitations. In this paper, a novel SD-6LN architecture has been proposed for existing IPv6 over Low Power Wireless Personal Area Network (6LoWPAN) based IoT infrastructure. The SD-6LN architecture incorporates the network layer of IoT and SDN to address some of the challenges of traditional resource constraint IoT network systems such as availability, reliability, scalability and resiliency. The experimentation was carried out in simulation. The experimental results indicated improved performance with respect to round trip time, jitter, packet drop, latency and throughput.